628 Cutaneous Sarcoidosis on a Three Years Old Child. (October 2012) - Bexiga, V; André, M; Silva, M; Afonso, A; Neto, AS
Abstract : Background: Sarcoidosis is a multisystemic granulomatous disorder characterized by the presence of noncaseating granulomas in tissues such as the skin, lung, lymph nodes, eyes, joints, brain, kidneys and heart. Sarcoidosis is a rare disease in paediatric age, with an incidence of 0.06/100.000 habitants, in children younger than four years of age. Cutaneous involvement is more common in the pediatric population than in adults. Skin may be involved in 80% of affected children. Case Report: The AA present the case of a three years old girl, with unremarkable personal or familiar medical background, that presented a facial nonexsudative maculopapular lesion after insect bite. Four months later, in spite of various therapeutic approaches, the lesion was larger with erythematous-violaceous papules. She had no systemic symptoms. The patient was referred to dermatology. Skin biopsy identified histopathologic features consistent with sarcoidosis. Pulmonar and ophthalmologic examination were normal. Serum angiotensin converting enzyme level was elevated. She started oral prednisolone 1mg/kg/d with clinical improvement after one month. Conclusion: Dermatological manifestations of sarcoidosis should be considered in differential diagnosis of various chronic skin conditions such as eczema, acne or infections. The risk of development of systemic sarcoidosis in patients who present with the disease limited to the skin is unknown. However studies have shown that younger children have more risk of develop more serious sequelae.